Oracle database application security : with Oracle Internet Directory, Oracle Access Manager, and Oracle Identity Manager /: with Oracle Internet Directory, Oracle Access Manager, and Oracle Identity Manager. ([2019]) - Mustafa, Osama; Lockard, Robert P
No abstract available